2016
DOI: 10.1016/j.jneumeth.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Automated segmentation and enhancement of optical coherence tomography-acquired images of rodent brain

Abstract: Background Optical coherence tomography (OCT) is a non-invasive optical imaging method that has proven useful in various fields such as ophthalmology, dermatology and neuroscience. In ophthalmology, significant progress has been made in retinal layer segmentation and enhancement of OCT images. There are also segmentation algorithms to separate epidermal and dermal layers in OCT-acquired images of human skin. New Method We describe simple image processing methods that allow automatic segmentation and enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…[20][21][22] The high resolution of third-generation spectral-domain OCT devices renders in vivo retinal imaging in mice and rats possible, gaining an increasing importance in ophthalmological and neurological preclinical research. [23][24][25][26][27][28][29][30][31][32][33] The obtained results are in good accordance with histological sections of the animals' retinae. 34 The application of OCT technology in rodent models, however, is still challenging, mainly because of the small size of the rodents' eyes.…”
Section: Introductionsupporting
confidence: 82%
“…[20][21][22] The high resolution of third-generation spectral-domain OCT devices renders in vivo retinal imaging in mice and rats possible, gaining an increasing importance in ophthalmological and neurological preclinical research. [23][24][25][26][27][28][29][30][31][32][33] The obtained results are in good accordance with histological sections of the animals' retinae. 34 The application of OCT technology in rodent models, however, is still challenging, mainly because of the small size of the rodents' eyes.…”
Section: Introductionsupporting
confidence: 82%
“…A fiber-based 1340nm spectral domain OCT system [24] was used for the capillary velocimetry experiments. The light source was a superluminescent diode (LS2000C, Thorlabs Inc.) with a spectral bandwidth of 110nm at the full-wavelength width at half maximum, yielding the axial (depth) resolution of ~7ÎŒm in tissue.…”
Section: System Descriptionmentioning
confidence: 99%
“…The body temperature of mouse was maintained at 36.8°C by a heating blanket on the frame whose temperature was controlled by a homeothermic monitoring system (50-7220F, Harvard Apparatus) that continually monitored the body temperature using rectal insertion of a temperature-sensing probe. Under anesthesia, the mice received open skull craniotomy [24], where a 4mm × 4mm area of the skull over the somatosensory cortex in right hemisphere was removed along with the dura and then the exposed somatosensory cortex was covered with a 5-mm-diameter transparent glass coverslip. The cranial window covers the territories supplied by the anterior cerebral artery (ACA) and middle cerebral artery (MCA), and anastomoses.…”
Section: Animal Preparationmentioning
confidence: 99%
“…Recent development of OCT-based angiography has started to shed some new light on cerebral hemodynamics in neuroscience. Baran et al demonstrated the effectiveness of proposed automatic image segmentation and enhancement methods for OCT-based microangiography (OMAG) and tissue injury mapping (TIM) in a mouse cerebral cortex (50,51).…”
Section: Brain Imaging and 'Biopsy'with Oct Systemmentioning
confidence: 99%